Preparation method and application of silicon-carbon negative electrode material

By covering silicon and carbon layers in the negative electrode material of the battery, the volume expansion problem of silicon material is solved, the cycle life and energy density of the battery are improved, and efficient electrochemical performance and low-cost preparation are achieved.

CN119284870APending Publication Date: 2025-01-10HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411366214.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The volume expansion of silicon material during the battery cycle leads to battery bond damage, and the cycle performance and safety decreases. The existing technology increases energy density and preparation costs when improving cycle life.

Method used

By placing the template agent in a silicon-containing atmosphere, and then coating the carbon layer with a carbon source, removing the template agent with an organic solvent, a hollow structure of silicon carbon anode material is prepared, which has both high energy density and high Cyclic performance.

Benefits of technology

The high energy density and excellent cycle performance of silicon carbon anode material are achieved, the cycle life and safety performance of the battery are improved, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284870A_ABST
    Figure CN119284870A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a silicon-carbon negative electrode material, and the preparation method comprises the following steps: placing a template agent in a silicon-containing atmosphere, and coating the surface of the template agent with a silicon layer through a first reaction to obtain a silicon-containing material; mixing the silicon-containing material with a carbon source, and coating the surface of the silicon-containing material with a carbon layer through a second reaction to obtain a silicon-carbon negative electrode material precursor; and dissolving the silicon-carbon negative electrode material precursor in an organic solvent, and removing the template agent to obtain the silicon-carbon negative electrode material. The preparation method provided by the invention is novel, the preparation process is simple, the silicon-carbon negative electrode material with energy density and cycle performance can be prepared, and the electrochemical performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and specifically to a preparation method and application of silicon-carbon negative electrode materials. Background Art

[0002] At present, silicon materials have excellent specific capacity and have become a research hotspot for negative electrode materials. However, during the battery cycle, the silicon material will expand in volume, resulting in the destruction of the battery bonding, and the battery's cycle performance, capacity and safety will be greatly reduced. In the related technology, silicon can be deposited on the surface of porous carbon materials to obtain silicon-carbon negative electrode materials. In silicon-carbon negative electrode materials, in order to alleviate the volume expansion of silicon materials and increase the cycle life of silicon-carbon negative electrode materials, the content of porous carbon materials is increased, but this will cause the energy density of silicon-carbon negative electrode materials to decrease and the preparation cost to increase. Therefore, there is a need for a method for preparing a silicon-carbon negative electrode material with both high energy density and high cycle performance to improve the electrochemical performance of the battery. Summary of the invention

[0003] In view of this, the present application provides a preparation method and application of a silicon-carbon negative electrode material, which can produce a silicon-carbon negative electrode material with both high energy density and high cycle performance, which is beneficial to improving the cycle life and battery capacity of the battery.

[0004] In a first aspect, the present application provides a method for preparing a silicon-carbon negative electrode material, comprising: placing a template in a silicon-containing atmosphere, coating a silicon layer on the surface of the template through a first reaction, to obtain a silicon-containing material; mixing the silicon-containing material with a carbon source, coating a carbon layer on the surface of the silicon-containing material through a second reaction, to obtain a silicon-carbon negative electrode material precursor; dissolving the silicon-carbon negative electrode material precursor in an organic solvent, and removing the template to obtain a silicon-carbon negative electrode material.

[0005] Optionally, the template includes one or more of calcium chloride, magnesium chloride and copper chloride.

[0006] Optionally, the silicon-containing atmosphere includes at least one of monosilane, disilane, monochlorotrihydrogensilane, dichlorodihydrogensilane and trichloromonohydrogensilane, and the flow rate of the silicon-containing atmosphere is 5 L / min-20 L / min.

[0007] Optionally, the temperature of the first reaction is 420°C-600°C, and the time of the first reaction is 27min-200h.

[0008] Optionally, the carbon source includes at least one of acetylene, propyne, methane and ethylene, and the flow rate of the carbon source is 5 L / min-20 L / min.

[0009] Optionally, the temperature of the second reaction is 500°C-580°C, and the time of the second reaction is 20 min-10 h.

[0010] Optionally, the organic solvent includes one or more of anhydrous ethanol, glacial acetic acid, methanol, isopropanol, n-propanol, n-butanol, and glycerol.

[0011] Optionally, the shape of the template includes one or more of spherical, linear and flake shapes.

[0012] Optionally, the Dv50 of the template is 50nm-22μm.

[0013] Optionally, after mixing the silicon-containing material with the carbon source and subjecting the mixture to a second reaction, the method further comprises: introducing an inert gas and performing a heat treatment to obtain a silicon-carbon negative electrode material precursor.

[0014] Optionally, the temperature of the heat treatment is greater than or equal to 800° C., and the time of the heat treatment is greater than or equal to 3 hours.

[0015] The preparation method provided in the present application is novel, the preparation process is simple, the preparation cost is low, and the prepared silicon-carbon negative electrode material has both high energy density and high cycle stability.

[0016] In a second aspect, the present application provides a silicon-carbon negative electrode material, which is prepared by the preparation method described in the first aspect, and the silicon-carbon negative electrode material is sequentially provided with a hollow core, a silicon layer and a carbon layer from the inside to the outside.

[0017] Optionally, in the silicon-carbon negative electrode material, the mass percentage of the silicon layer is 30%-99.999%, and the mass percentage of the carbon layer is 0.001%-70%.

[0018] Optionally, the volume percentage of the hollow core is 30%-80%.

[0019] Optionally, the specific surface area of ​​the silicon-carbon negative electrode is 0.1 m 2 g -1 -100m 2 g -1 .

[0020] Optionally, the Dv50 particle size of the silicon-carbon negative electrode material is 54nm-23μm, and the thickness of the carbon layer is 2nm-10nm.

[0021] Optionally, the silicon layer includes one or more of crystalline silicon and amorphous silicon.

[0022] The silicon-carbon negative electrode material provided in the present application has a hollow structure, which provides space for the volume expansion of the silicon material, thereby improving the cycle life of the silicon-carbon negative electrode material. The appropriate proportion of carbon material and silicon material is conducive to improving the energy density of the silicon-carbon negative electrode material, so that the silicon-carbon negative electrode material has both high energy density and excellent cycle performance.

[0023] In a third aspect, the present application provides a negative electrode plate, which includes the silicon-carbon negative electrode material prepared by the preparation method described in the first aspect or the silicon-carbon negative electrode material described in the second aspect.

[0024] The negative electrode plate provided in the present application has high energy density and good cycle performance, which is beneficial to improving the safety and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0026] Figure 1 A schematic diagram of the cross-sectional structure of a silicon-carbon negative electrode material provided in one embodiment of the present application;

[0027] Figure 2 A schematic diagram of the cross-sectional structure of a negative electrode plate provided in one embodiment of the present application. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0029] The present application provides a method for preparing a silicon-carbon negative electrode material, including placing a template in a silicon-containing atmosphere, coating a silicon layer on the surface of the template through a first reaction to obtain a silicon-containing material; mixing the silicon-containing material with a carbon source, coating a carbon layer on the surface of the silicon-containing material through a second reaction to obtain a silicon-carbon negative electrode material precursor; dissolving the silicon-carbon negative electrode material precursor in an organic solvent, and removing the template to obtain a silicon-carbon negative electrode material. In the present application, a silicon layer is coated on the surface of the template to obtain a silicon-containing material, the silicon-containing material is mixed with a carbon source, and a carbon layer is coated on the surface of the silicon-containing material to obtain a silicon-carbon negative electrode material precursor, the silicon-carbon negative electrode material precursor is cleaned with an organic solvent, and the template is removed to form a hollow structured silicon-carbon negative electrode material; using a template with a high melting point and soluble in an organic solvent, the template is easily removed during the preparation of the silicon-carbon negative electrode material, so that the silicon-carbon negative electrode material has both high energy density and excellent cycle performance, improves the comprehensive performance of the silicon-carbon negative electrode material, and is conducive to improving the cycle life and safety performance of the battery.

[0030] In one embodiment of the present application, the melting point of the template is higher than the cracking temperature of the silicon-containing atmosphere, and it is easily soluble in an organic solvent, which can ensure that when silicon is coated in a silicon-containing atmosphere, the template remains stable and does not melt, which is conducive to the formation of a hollow structured silicon-carbon negative electrode material. Specifically, the template may include, but is not limited to, one or more of calcium chloride, magnesium chloride, and copper chloride. In one embodiment of the present application, the template may be calcium chloride. In another embodiment of the present application, the template may be copper chloride.

[0031] In one embodiment of the present application, the shape of the template determines the shape of the silicon-carbon negative electrode material, which can be selected according to actual needs. Specifically, the template can be a solid structure, for example, the shape of the template can be but is not limited to one or more of spherical, linear and flaky. In one embodiment of the present application, the template can be spherical, and the obtained silicon-carbon negative electrode material can be spherical. In another embodiment of the present application, the template can be linear, and the obtained silicon-carbon negative electrode material is also linear.

[0032] In one embodiment of the present application, when the shape of the template is spherical, the spherical Dv50 particle size is 100nm-500nm, and the appropriate template size can increase the compaction density of the silicon-carbon negative electrode material and increase the energy density of the silicon-carbon negative electrode material. Specifically, the Dv50 particle size of the template can be, but is not limited to, 100nm, 150nm, 200nm, 250nm, 300nm, 400nm or 500nm, etc. In one embodiment of the present application, the Dv50 particle size of the template can be 100nm-150nm. In another embodiment of the present application, the Dv50 particle size of the template can be 400nm-500nm.

[0033] In one embodiment of the present application, the template may be a porous structure, and the Dv50 particle size of the porous template is 50nm-22μm. Specifically, the Dv50 particle size of the porous template may be, but is not limited to, 50nm, 100nm, 200nm, 500nm, 1μm, 5μm, 10μm or 22μm, etc. In one embodiment of the present application, the Dv50 particle size of the porous template may be 550nm-10μm. In another embodiment of the present application, the Dv50 particle size of the porous template may be 10μm-22μm.

[0034] In one embodiment of the present application, the silicon-containing atmosphere can form a silicon layer on the surface of the template to improve the energy density of the silicon-carbon negative electrode material. Specifically, the silicon-containing atmosphere can include, but is not limited to, one or more of monosilane (SiH4), disilane (Si2H6), monochlorotrihydrogen silicon (SiH3Cl), dichlorodihydrogen silicon (SiH2Cl) and trichloromonohydrogen silicon (SiHCl3). In one embodiment of the present application, the silicon-containing atmosphere can be monosilane.

[0035] In one embodiment of the present application, the flow rate of the silicon-containing atmosphere is 1L / min-30L / min. A suitable flow rate of the silicon-containing atmosphere can form a silicon layer of suitable thickness on the surface of the template, which is beneficial to improve the energy density of the silicon-carbon negative electrode material. Specifically, the flow rate of the silicon-containing atmosphere can be but is not limited to 1L / min, 5L / min, 8L / min, 10L / min, 12L / min, 15L / min, 20L / min or 30L / min, etc. In one embodiment of the present application, the flow rate of the silicon-containing atmosphere can be 1L / min-5L / min. In another embodiment of the present application, the flow rate of the silicon-containing atmosphere can be 10L / min-30L / min. In the present application, the selection of the use flow rate of the silicon-containing atmosphere needs to be adjusted according to the reactor diameter.

[0036] In one embodiment of the present application, the temperature of the first reaction is 420°C-600°C, and the time of the first reaction is 27min-200h. Appropriate reaction time and temperature can make the silicon-containing atmosphere form a silicon layer with strong bonding force and suitable thickness on the surface of the template, thereby improving the structural stability of the silicon-carbon negative electrode material. Specifically, the temperature of the first reaction may be, but is not limited to, 420°C, 450°C, 480°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or 600°C, and the time of the first reaction may be, but is not limited to, 27min, 1h, 2h, 5h, 10h, 15h, 30h, 60h, 90h, 150h or 200h, etc. In one embodiment of the present application, the temperature of the first reaction may be 420°C-500°C, and the time of the first reaction may be 27min-125h. In another embodiment of the present application, the temperature of the first reaction may be 500° C.-600° C., and the time of the first reaction may be 117 h-200 h.

[0037] In one embodiment of the present application, before the silicon-containing atmosphere is introduced, an inert atmosphere is introduced for gas washing, and the flow rate of the inert atmosphere is 50L / min-100L / min, which can improve the safety of the reaction and the purity of the silicon-carbon negative electrode material. Specifically, the flow rate of the inert atmosphere can be, but is not limited to, 50L / min, 55L / min, 60L / min, 65L / min, 70L / min, 80L / min or 100L / min, etc. In one embodiment of the present application, the inert gas can be nitrogen, and the flow rate of nitrogen can be 60L / min.

[0038] In one embodiment of the present application, the carbon source can form a carbon layer on the surface of the silicon-containing material, which can improve the conductivity of the silicon-carbon negative electrode material. Specifically, the carbon source can be one or more of a solid phase, a liquid phase, and a gas phase, including but not limited to one or more of asphalt, tar, resin, polymer, alkane, alkene, alkyne, and aromatic hydrocarbon.

[0039] In one embodiment of the present application, the carbon source may include, but is not limited to, one or more of acetylene, propyne, methane, and ethylene. In one embodiment of the present application, the carbon source may be acetylene.

[0040] In one embodiment of the present application, when the carbon source is in gas phase, the flow rate of the carbon source is 5L / min-20L / min. A suitable carbon source flow rate can form a carbon layer of suitable thickness on the surface of the silicon-containing material, which is beneficial to improve the structural stability and conductivity of the silicon-carbon negative electrode material. Specifically, the flow rate of the carbon source can be but is not limited to 5L / min, 8L / min, 10L / min, 12L / min, 15L / min, 18L / min or 20L / min, etc. In one embodiment of the present application, the flow rate of the carbon source can be 5L / min-15L / min. In another embodiment of the present application, the flow rate of the carbon source can be 10L / min-20L / min. In the present application, the selection of the use flow rate of the carbon source needs to be adjusted according to the reactor diameter.

[0041] In one embodiment of the present application, the temperature of the second reaction is 500°C-580°C, and the time of the second reaction is 20min-10h. Appropriate reaction time and temperature can make the carbon source form a carbon layer with strong bonding and suitable thickness on the surface of the silicon-containing material, thereby improving the conductivity and structural stability of the silicon-carbon negative electrode material. Specifically, the temperature of the second reaction may be, but is not limited to, 500°C, 520°C, 540°C, 550°C, 555°C, 560°C, 565°C, 570°C or 580°C, and the time of the second reaction may be, but is not limited to, 20min, 30min, 40min, 50min, 1h, 5h, 8h or 10h, etc. In one embodiment of the present application, the temperature of the second reaction may be 550°C-570°C, and the time of the second reaction may be 20min-4h. In another embodiment of the present application, the temperature of the second reaction may be 560°C-580°C, and the time of the second reaction may be 4h-10h.

[0042] In one embodiment of the present application, before the carbon source is introduced, an inert atmosphere may be introduced for gas washing, and the flow rate of the inert atmosphere is 50L / min-100L / min, which can improve the safety of the reaction and the purity of the silicon-carbon negative electrode material. Specifically, the flow rate of the inert atmosphere may be, but is not limited to, 50L / min, 55L / min, 60L / min, 65L / min, 70L / min, 80L / min or 100L / min, etc. In one embodiment of the present application, the inert gas may be nitrogen, and the flow rate of the nitrogen may be 60L / min.

[0043] In one embodiment of the present application, the silicon-containing material is mixed with a carbon source, and after the second reaction, it also includes: introducing an inert gas, performing heat treatment to obtain a silicon-carbon negative electrode material precursor, the temperature of the heat treatment is greater than or equal to 800°C, and the time of the heat treatment is greater than or equal to 3h. The heat treatment can transform the silicon material in the silicon-carbon negative electrode material precursor on the surface from amorphous silicon to crystalline silicon, and at the same time increase the carbonization degree of the carbon material, which is beneficial to improve the rate performance of the battery. Specifically, the temperature of the heat treatment may be, but is not limited to, greater than or equal to 800°C, greater than or equal to 850°C, greater than or equal to 900°C, greater than or equal to 950°C, or greater than or equal to 1000°C, etc.; the time of the heat treatment may be, but is not limited to, greater than or equal to 3h, greater than or equal to 3.5h, greater than or equal to 4h, greater than or equal to 4.5h, or greater than or equal to 5h, etc. In one embodiment of the present application, the temperature of the heat treatment may be greater than or equal to 800°C, and the time of the heat treatment may be greater than or equal to 3h. In another embodiment of the present application, the temperature of the heat treatment may be greater than or equal to 900° C., and the time of the heat treatment may be greater than or equal to 5 hours.

[0044] In one embodiment of the present application, after the second reaction, an inert gas is introduced and naturally cooled to obtain a silicon-carbon negative electrode material precursor. At this time, the silicon material is amorphous silicon and the carbon material maintains an appropriate degree of carbonization, which is beneficial to alleviate the volume expansion of the silicon-carbon negative electrode material during the cycle and improve the cycle stability and service life of the battery.

[0045] In one embodiment of the present application, the reaction device may be, but is not limited to, a fluidized bed, a rotary kiln, etc. In one embodiment of the present application, the reaction device may be a fluidized bed.

[0046] In one embodiment of the present application, an organic solvent is used to remove the template in the silicon-carbon negative electrode material precursor to obtain a silicon-carbon negative electrode material, and the removed template can be recycled for a second time, further reducing the preparation cost. Specifically, the organic solvent may include, but is not limited to, one or more of anhydrous ethanol, glacial acetic acid, methanol, isopropanol, n-propanol, n-butanol, and glycerol. In one embodiment of the present application, the organic solvent may be anhydrous ethanol. In another embodiment of the present application, the organic solvent is a non-oxidizing organic solvent.

[0047] See also Figure 1 , is a schematic diagram of the cross-sectional structure of a silicon-carbon negative electrode material provided in one embodiment of the present application. The silicon-carbon negative electrode material 100 is provided with a hollow core 10, a silicon layer 11 and a carbon layer 12 in sequence from the inside to the outside. The silicon-carbon negative electrode material prepared by the preparation method provided in the present application is a hollow structure, which can alleviate the volume expansion of the silicon material in the silicon layer, which is conducive to improving the energy density and cycle performance of the silicon-carbon negative electrode material. The carbon layer can improve the structural stability and conductivity of the silicon-carbon negative electrode material, and further improve the energy density, cycle performance and service life of the battery.

[0048] In one embodiment of the present application, the Dv50 particle size of the silicon-carbon negative electrode material is 54nm-23μm. The appropriate particle size can improve the compaction performance of the silicon-carbon negative electrode material and improve the compaction density of the negative electrode sheet. Specifically, the Dv50 particle size of the silicon-carbon negative electrode material can be, but is not limited to, 54nm, 100nm, 150nm, 200nm, 500nm, 1μm, 5μm, 10μm, 20μm or 23μm, etc. In one embodiment of the present application, the Dv50 particle size of the silicon-carbon negative electrode material can be 54nm-10μm. In another embodiment of the present application, the Dv50 particle size of the silicon-carbon negative electrode material can be 10μm-23μm.

[0049] In one embodiment of the present application, in the silicon-carbon negative electrode material, the mass percentage of the silicon layer is 30%-99.999%, which is beneficial to improve the capacity and electrochemical performance of the silicon-carbon negative electrode material. Specifically, in the silicon-carbon negative electrode material, the mass percentage of the silicon layer can be, but is not limited to, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99.999%, etc. In one embodiment of the present application, the mass percentage of the silicon layer is 40%-70%.

[0050] In one embodiment of the present application, the silicon layer may include, but is not limited to, one or more of crystalline silicon and amorphous silicon.

[0051] In one embodiment of the present application, in the silicon-carbon negative electrode material, the volume percentage of the hollow core is 30%-80%. The appropriate volume percentage of the hollow core can provide expansion space for the silicon material, while increasing the compaction density of the silicon-carbon negative electrode material and improving the energy density of the negative electrode sheet. Specifically, in the silicon-carbon negative electrode material, the volume percentage of the hollow core can be but is not limited to 30%, 40%, 50%, 60%, 70% or 80%, etc. In one embodiment of the present application, in the silicon-carbon negative electrode material, the volume percentage of the hollow core is 40%-70%.

[0052] In one embodiment of the present application, in the silicon-carbon negative electrode material, the mass percentage of the carbon layer is 0.001%-70%, and a suitable carbon layer can improve the structural stability and conductive performance of the silicon-carbon negative electrode material. Specifically, the mass percentage of the carbon layer can be, but is not limited to, 0.001%, 1%, 10%, 20%, 30%, 40%, 50%, 60% or 70%, etc. In one embodiment of the present application, the mass percentage of the carbon layer is 30%-50%.

[0053] In one embodiment of the present application, the thickness of the carbon layer is 2nm-10nm. The appropriate thickness of the carbon layer can improve the structural stability and conductivity of the silicon-carbon negative electrode material. Specifically, the thickness of the carbon layer can be, but is not limited to, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm. In one embodiment of the present application, the thickness of the carbon layer can be 2nm-7nm. In another embodiment of the present application, the thickness of the carbon layer can be 5nm-10nm.

[0054] In one embodiment of the present application, the specific surface area of ​​the silicon-carbon negative electrode material is 0.1 m 2 g -1 -100m 2 g -1 The appropriate specific surface area can improve the electrochemical performance of the battery. Specifically, the specific surface area of ​​the silicon-carbon negative electrode material can be, but is not limited to, 0.1 m 2 g -1 , 1m 2 g -1 、10m 2 g -1 、20m 2 g -1 、30m 2 g -1 、40m 2 g -1 、50m 2 g -1 、60m 2 g -1 、70m 2 g -1 、80m 2 g -1 、90m 2 g -1 or 100m 2 g -1 In one embodiment of the present application, the specific surface area of ​​the silicon-carbon negative electrode material can be 0.1 m 2 g -1 -60m 2 g -1 In another embodiment of the present application, the specific surface area of ​​the silicon-carbon negative electrode material can be 50 m 2 g -1 -100m 2 g -1 .

[0055] The present application provides a negative electrode sheet, which includes the silicon-carbon negative electrode material described in any one of the above embodiments as a negative electrode active material, thereby improving the conductivity, cycle stability and rate performance of the negative electrode sheet. Figure 2, is a schematic diagram of the cross-sectional structure of a negative electrode plate provided in one embodiment of the present application. The negative electrode plate 200 includes a negative electrode current collector 20 and a negative electrode active material layer 21 disposed on the surface of the negative electrode current collector 20, and the negative electrode active material layer 21 includes the silicon-carbon negative electrode material described in any of the above embodiments. The negative electrode plate provided in the present application has good fast charging performance, good low temperature performance, and high cycle stability.

[0056] In one embodiment of the present application, the negative electrode current collector may include, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the negative electrode current collector may be copper foil.

[0057] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode conductive agent, which can increase the conductivity of the negative electrode material and improve the electronic conductivity. Specifically, the negative electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.

[0058] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode binder, which can improve the binding ability of the components in the negative electrode active material layer and improve the binding ability between the negative electrode active material layer and the current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride. In another embodiment of the present application, the negative electrode binder can be sodium carboxymethyl cellulose.

[0059] The present application also provides a battery, comprising a positive electrode sheet and a negative electrode sheet provided by any one of the above embodiments. The negative electrode sheet has a long cycle life and good fast charging performance, so the battery provided by the present application has excellent charging and discharging performance, good low temperature performance, and long service life.

[0060] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0061] In one embodiment of the present application, the positive electrode current collector may be, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the positive electrode current collector may be aluminum foil.

[0062] In one embodiment of the present application, the positive electrode active material can improve the conductivity, capacity and cycle stability of the positive electrode plate. The specific positive electrode active material can include but is not limited to at least one of lithium iron phosphate material, lithium iron manganese phosphate, lithium cobalt oxide material, lithium manganese oxide material, nickel cobalt manganese material and nickel cobalt aluminum material. In one embodiment of the present application, the positive electrode active material can be a lithium cobalt oxide material.

[0063] In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode conductive agent. The positive electrode conductive agent can increase the conductivity between the active materials and improve the electronic conductivity. Specifically, the positive electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the positive electrode conductive agent may be graphite. In another embodiment of the present application, the positive electrode conductive agent may be carbon black.

[0064] In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode binder, which can improve the binding ability of the components in the positive electrode active material layer and improve the binding ability between the positive electrode active material layer and the positive electrode current collector. Specifically, the positive electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the positive electrode binder can be polyvinylidene fluoride.

[0065] In one embodiment of the present application, the battery further includes a separator disposed between the positive electrode sheet and the negative electrode sheet. Specifically, the separator may be, but is not limited to, a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane, or a separator paper. In one embodiment of the present application, the battery further includes an electrolyte. Among them, at least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and may be, but is not limited to, a substance that can be used as a battery electrolyte in the art.

[0066] The present application also provides an electric device, which includes a battery provided by any of the above-mentioned embodiments. The electric device provided by the present application has excellent comprehensive performance and strong market competitiveness. The electric device of the present application may refer to a vehicle, an electronic device, an energy storage system, etc. In one embodiment of the present application, the battery can be used in a vehicle to increase the charging speed of the vehicle's electricity. In another embodiment of the present application, the battery can also be used in an electronic device to increase the cycle stability of the electronic device battery and improve the low-temperature performance of the battery.

[0067] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0068] Example 1

[0069] 5 kg of template (spherical particles of anhydrous calcium chloride with a Dv50 particle size of 100 nm) was put into a fluidized bed, nitrogen was introduced at a flow rate of 60 L / min, oxygen in the fluidized bed was discharged to below 20 ppm, the fluidized bed was heated to 500°C, kept warm for 30 min, silane was introduced at a flow rate of 2 L / min, a first reaction was carried out, the first reaction time was 16 h, 13 min, kept warm for 30 min, the temperature was raised to 580°C, kept warm for 30 min, acetylene was introduced at a flow rate of 10 L / min, a second reaction was carried out, the second reaction time was 30 min, heating was stopped, the temperature was cooled to room temperature, and nitrogen was turned off to obtain a silicon-carbon negative electrode material precursor;

[0070] The silicon-carbon negative electrode material precursor was fully washed three times in an organic solvent (anhydrous ethanol) to remove the template agent, centrifuged, and then fully dried in a vacuum oven at 80° C. to obtain the silicon-carbon negative electrode material.

[0071] Example 2

[0072] The difference from Example 1 is that the first reaction time is 15h, 20min, and after the second reaction, the temperature is raised to 800°C, and an inert gas (nitrogen) is introduced for heat treatment, and the heat treatment time is 2h.

[0073] Example 3

[0074] The difference from Example 1 is that the template agent is magnesium chloride.

[0075] Example 4

[0076] The difference from Example 1 is that the time of the first reaction is 32h, 25min.

[0077] Example 5

[0078] The difference from Example 1 is that the calcium chloride used has a Dv50 particle size of 500 nm, the silane flow rate is 20 L / min, and the first reaction time is 162 h, 5 min.

[0079] Comparative Example 1

[0080] The difference from Example 1 is that porous carbon is used instead of the template, the porous carbon cannot be removed by an organic solvent, and the prepared silicon-carbon negative electrode material has a solid structure.

[0081] Performance Testing

[0082] The silicon-carbon negative electrode materials prepared in the above Examples 1-5 and Comparative Example 1 were tested for particle size and thickness of the carbon layer according to GB / T24533-2019, and the results are shown in Table 1.

[0083] The specific surface area of ​​the silicon-carbon negative electrode materials prepared in the above Examples 1-5 and Comparative Example 1 was tested according to GB / T19587-2017, and the results are shown in Table 1.

[0084] Preparation of button half-cell: The silicon-carbon negative electrode material, conductive additive carbon black, and adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) prepared in the above Examples 1-5 and Comparative Example 1 are weighed according to a mass ratio of 94:2:4, and slurry is prepared with a beater to obtain negative electrode slurry; then the above negative electrode slurries are coated on the surface of the negative electrode current collector (specifically copper foil), and then dried and cut into pieces in turn, and assembled into button batteries with lithium metal sheets in a glove box. At a constant temperature of 25±2℃, a constant current charge and discharge mode test is performed using a charge and discharge instrument, the discharge cut-off voltage is 0.005V, and the charge cut-off voltage is 2V. The first week of charge and discharge test is performed at a current density of 1C / 10 to obtain the charge capacity and discharge capacity, and the charge capacity is recorded as the reversible gram capacity.

[0085] Preparation of a full battery: The silicon-carbon negative electrode material obtained in the above embodiments 1-5 and comparative example 1 is configured with graphite to form a composite with a specific capacity of 450mAg / h, and then mixed with a conductive additive and a binder at a mass ratio of 94:2:4 to prepare a negative electrode slurry, and the negative electrode slurry is coated on a current collector (specifically copper foil) to obtain a negative electrode sheet; the positive electrode active material ternary NMC532, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a weight ratio of 96.7:1.7:1.6, and then coated on an Al foil, dried, and cold pressed to obtain a positive electrode sheet; a polypropylene porous polymer film is used as an isolation film; the above-mentioned positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is between the positive electrode sheet and the negative electrode sheet to play an isolation role, and then wound to obtain a bare battery cell. The bare cell is placed in the outer packaging, injected with the prepared electrolyte and packaged, and the full cell is obtained through the process of formation, degassing, trimming, etc. The electrolyte is a common silicon negative electrode electrolyte formula on the market.

[0086] The full batteries prepared in the above-mentioned Examples 1-5 and Comparative Example 1 were subjected to battery expansion test and battery expansion rate test: at 25°C, the above-mentioned full batteries were subjected to constant current charge and discharge test using a charge and discharge instrument, with a discharge cut-off voltage of 2.75V and a charge cut-off voltage of 4.2V. The charge and discharge tests were all conducted at a current density of 1C. After 100 cycles, the expansion rate of each battery was determined using an in-situ expansion analysis system, and the results are summarized in Table 2. The capacity retention rate after 300 cycles was also recorded, and the capacity retention rate = discharge capacity of the 300th cycle / discharge capacity of the 1st cycle × 100%. The test results are shown in Table 2.

[0087] The half-cells prepared in the above-mentioned Examples 1-5 and Comparative Example 1 were subjected to rate performance tests. Rate performance tests: At 25°C, a charge and discharge instrument was used to perform constant current charge and discharge tests on the above-mentioned full cells. The discharge cut-off voltage was 1mV, the charge cut-off voltage was 1.5V, and the charge and discharge tests were performed at current densities of 0.1C, 0.5C, 1C, 3C, and 5C, respectively. Rate performance = charging capacity at the corresponding rate current density / charging capacity at 0.1C current density × 100%. The test results are shown in Table 2.

[0088] Table 1 Performance test results of silicon-carbon negative electrode materials

[0089]

[0090] Table 2 Battery performance test results

[0091]

[0092] It can be seen from Examples 1-5 and Comparative Example 1 that the preparation method of the silicon-carbon negative electrode material provided in the present application can prepare a silicon-carbon negative electrode material having a hollow core, a silicon layer and a carbon layer, and can obtain a silicon-carbon negative electrode material having both high energy density and high cycle performance. It can be seen from Examples 1-5 that suitable conditions for the first reaction and the second reaction, template selection, and particle size, etc., are conducive to obtaining a silicon-carbon negative electrode material with high energy density, good cycle performance, and long service life. It can be seen from Example 1 and Comparative Example 1 that a silicon-carbon negative electrode material with a hollow structure of suitable volume can alleviate the volume expansion of the silicon layer, improve the structural stability of the negative electrode material, and is conducive to improving the cycle life, rate performance and capacity retention rate of the battery, reducing the expansion rate of the battery, and is conducive to the wide application of the battery.

[0093] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: include: placing the template in a silicon-containing atmosphere, and coating the surface of the template with a silicon layer through a first reaction to obtain a silicon-containing material; The silicon-containing material is mixed with a carbon source, and a carbon layer is coated on the surface of the silicon-containing material through a second reaction to obtain a silicon-carbon negative electrode material precursor; The silicon-carbon negative electrode material precursor is dissolved in an organic solvent, and the template agent is removed to obtain the silicon-carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that The template includes one or more of calcium chloride, magnesium chloride and copper chloride.

3. The preparation method according to claim 1, characterized in that: The silicon-containing atmosphere comprises one or more of monosilane, disilane, monochlorotrihydrogensilane, dichlorodihydrogensilane and trichloromonohydrogensilane, and the flow rate of the silicon-containing atmosphere is 1 L / min-30 L / min; The temperature of the first reaction is 420° C.-600° C., and the time of the first reaction is 27 min-200 h.

4. The preparation method according to claim 1, characterized in that: The carbon source includes one or more of acetylene, propyne, methane, and ethylene, and the flow rate of the carbon source is 5L / min-20L / min; The temperature of the second reaction is 500° C.-580° C., and the time of the second reaction is 20 min-10 h.

5. The preparation method according to claim 1, characterized in that: The organic solvent includes one or more of anhydrous ethanol, methanol, isopropanol, n-propanol, n-butanol, glycerol, and glacial acetic acid.

6. The preparation method according to claim 1, characterized in that: The Dv50 of the template is 50nm-22μm.

7. The preparation method according to claim 1, characterized in that: After the silicon-containing material and the carbon raw material are mixed and subjected to a second reaction, the method further comprises: introducing an inert gas and performing a heat treatment to obtain a silicon-carbon negative electrode material precursor; The temperature of the heat treatment is greater than or equal to 800° C., and the time of the heat treatment is greater than or equal to 3 hours.

8. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material is prepared according to any one of the preparation methods of claims 1-7, and the silicon-carbon negative electrode material is sequentially provided with a hollow core, a silicon layer and a carbon layer from the inside to the outside.

9. The silicon-carbon negative electrode material according to claim 8, characterized in that: In the silicon-carbon negative electrode material, the mass percentage of the silicon layer is 30%-99.999%, and the mass percentage of the carbon layer is 0.001%-70%; The volume percentage of the hollow core is 30%-80%.

10. The silicon-carbon negative electrode material according to claim 9, characterized in that: The specific surface area of ​​the silicon-carbon negative electrode material is 0.1 m 2 g -1 -100m 2 g -1 ; The Dv50 particle size of the silicon-carbon negative electrode material is 54nm-23μm; the thickness of the carbon layer is 2nm-10nm.

11. The silicon-carbon negative electrode material according to claim 9, characterized in that: The silicon layer includes one or more of crystalline silicon and amorphous silicon.

12. A negative electrode plate, characterized in that: The negative electrode plate comprises a silicon-carbon negative electrode material prepared by the preparation method described in any one of claims 1 to 7 or a silicon-carbon negative electrode material described in any one of claims 8 to 11.